MEDIASI PENAL SEBAGAI ALTERNATIF PENYELESAIAN PERKARA TINDAK PIDANA PRAKTIK KEDOKTERAN - S. Tri Herlianto (Faculty of Law, Universitas Diponegoro, 2014)
The study aims to determine the concept of restorative justice in the implementation of penal mediation perspective of current legislation and also examines the implementation and construction legislasia policy in criminal law reform that will come. The research found that the concept of restorative justice, the presence and position of the victim as a patient admitted. Families of patients involved in the settlement of his case poses. Penal mediation is one form of implementation of restorative justice, namely the rehabilitation, resocialization, restitution, reparation and compensation to complete a criminal case of medical practice